Analysis of Impulsive Buying E-Commerce Shopee in Generation Z: A Conceptual Framework - Sihombing, Reni Pratiwi; Widodo, Arry; Rubiyanti, Nurafni; Silvianita, Anita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The ease of online shopping encourages consumers to buy various products they want so that they are encouraged to behave consumptuously. This then stimulates the phenomenon of impulse buying in consumers. This study aims to determine the relationship between hedonic shopping motivation, fear of missing out, shopping lifestyle and positive emotion towards impulse buying. The population of this study is generation Z men and women born in 1997-2012 who have made impulse purchases on the Shopee platform. The sample consists of generation Z of Shopee e-commerce users. The collected data will be analyzed using the Structural Equation Modeling (SEM) approach using the Smart PLS 3.0 SEM-PLS application. The results showed that hedonic shopping motivation, fear of missing out, shopping lifestyle and positive emotion as mediating factors had a significant and positive influence on impulse buying.